High-pressure behaviour of Prussian blue analogues: interplay of hydration, Jahn-Teller distortions and vacancies. Issue 5 (14th December 2018) - Boström, Hanna L. B.; Collings, Ines E.; Cairns, Andrew B.; Romao, Carl P.; Goodwin, Andrew L.
Abstract : Compression of Mn[Pt(CN)6 ] and its defective analogue Mn[Co(CN)6 ]0.67 leads to tilting, whereas no transition occurs for the orbitally disordered Cu[Co(CN)6 ]0.67 . Abstract : We report a high-pressure crystallographic study of four hydrated Prussian blue analogues: M[Pt(CN)6 ] and M[Co(CN)6 ]0.67 (M = Mn 2+, Cu 2+ ) in the range 0–3 GPa. Mn[Co(CN)6 ]0.67 was studied by single-crystal X-ray diffraction, whereas the other systems were only available in polycrystalline form. The Mn-containing compounds undergo pressure-induced phase transitions from Fm 3̄ m to R 3̄ at ∼1.0–1.5 GPa driven by cooperative tilting of the octahedral units. No phase transition was found for the orbitally disordered Cu[Co(CN)6 ]0.67 up to 3 GPa. Mn[Co(CN)6 ]0.67 is significantly softer than the other samples, with a bulk modulus of ∼14 GPa compared to ∼35 GPa of the powdered samples. The discrepant pressure responses are discussed in terms of the presence of structural defects, Jahn-Teller distortions, and hydration. The implications for the development of polar systems are reviewed based upon our high-pressure study.